Harvesting Hope: Empowering Farmers to thrive in Kenya Semi-Arid Lands - Mfalme Afrika Production Ltd (CGIAR System Organization, 2024)
Inequalities in agri-food systems in sub-Saharan Africa stem from unequal decision-making power, limited access to resources, and land ownership disparities. Climate change exacerbates these inequalities, disproportionately affecting women. Existing policies and governance systems have not adequately addressed these challenges. Socio-technical innovation bundles (STIBs) offer a potential solution by addressing climate change while challenging sociocultural norms perpetuating inequalities. The CGIAR Gender Equality Initiative (HER+) collaborated with the CGIAR Diversification in East and Southern Africa to enhance climate resilience and women's empowerment in Kenya through the STIBs approach. Adopting farmer-preferred STIBs, such as decision-making, gender and nutrition, certified seeds, climate-smart practices like intercropping, extension services, and financial access, led to higher productivity, resilience, and empowerment. Key outcomes included: sustained crop performance despite adverse climate conditions, increased household decision-making collaboration due to women’s greater farming knowledge and financial contributions, and improved food security through diversified diets and food accessibility. These results highlight progress toward equitable and resilient agri-food systems.